Glial Tiling in the Insect Nervous System - Pogodalla, Nicole; Winkler, Bente; Klämbt, Christian (Frontiers in Cellular Neuroscience, 2022)
The Drosophila nervous system is characterized by a small number of well characterized glial cell classes. The outer surface of the central nervous system (CNS) is protected by a glial derived blood-brain barrier comprising perineurial glia and subperineurial glia. All neural stem cells and all neurons are engulfed by cortex glial cells and the inner neuropil region, that harbors all synapses and dendrites is covered by ensheathing glia and infiltrated by astrocyte-like glial cells. All these glial cells show a tiled organization with an often remarkable plasticity where glial cells of one cell type invade the territory of the neighboring glial cell type upon its ablation. Here, we summarize the different glial tiling patterns and based on the different modes of cell-cell contacts we hypothesize that different molecular mechanisms underlie tiling of the different glial cell types.